Mobile robot programming in education - Lalonde, J.-F.; Hartley, C.P.; Nourbakhsh, I. (Proceedings 2006 IEEE International Conference on Robotics and Automation, 2006. ICRA 2006, 2006)
The mobile robot programming laboratory course has been taught at Carnegie Mellon University for the past twelve years. It is a problem-driven class designed for students with little or no experience with robots. In this paper, we first present the current status of the class, and show how it improves the education and training of students in a robotics curriculum by giving them a hands-on experience with a real robot. We show that, in addition to core subjects such as perception, action and cognition, students also have the opportunity to learn advanced topics such as reinforcement learning and multi-robot coordination. We then discuss the evolution of the class under general categories: hardware and programming environment, team experiments, and assignments. We present important lessons learned in each category, and how they affect the learning experience of participating students. We conclude by discussing future opportunities